Flights of passage An illustrated natural history of bird migration - Unwin,Mike; Unwin, Mike (New Haven Yale University Press, 2020)
In this luxuriously illustrated volume, celebrated nature writer Mike Unwin and award-winning photographer David Tipling highlight sixty-seven different species of birds from around the world and explore how each has adapted to its migratory cycle.